2013
DOI: 10.3171/2013.8.focus13258
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of passive helmet therapy for deformational plagiocephaly: report of 1050 cases

Abstract: Object There has been a tremendous increase in the incidence of deformational plagiocephaly in children throughout the world. Therapeutic options include observation, active counterpositioning, external orthotics, and surgery. The current treatment in the US is highly debated, but it typically includes external orthotic helmets in patients with moderate to severe plagiocephaly presenting between 4 and 10 months of age or in children with significant comorbidities lim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
23
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 24 publications
(26 reference statements)
0
23
0
Order By: Relevance
“…3,7,8 This age also falls in the ideal time for treatment, which is between 4 and 8 months, before the fontanels begin closing and the calvaria thickens approximately 9 to 12 months of age. 6 The most common comorbidities associated with DP in this study included prematurity, 11.1%; torticollis, 10.4%; pregnancy complication, 7.4%; twin or triplet, 6.6%; ear infections requiring tympanostomy tubes, 2.6%; cephalohematoma, 1.0%; family history, 0.6%; seizures, 0.6%; and hydrocephalus, 0.5% (Table 2). Risk factors for DP have been reported to include assisted delivery, 3,8,10,12 plural births, 12 prolonged labor, 12 intrauterine constraint, 2 or unusual birth position.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…3,7,8 This age also falls in the ideal time for treatment, which is between 4 and 8 months, before the fontanels begin closing and the calvaria thickens approximately 9 to 12 months of age. 6 The most common comorbidities associated with DP in this study included prematurity, 11.1%; torticollis, 10.4%; pregnancy complication, 7.4%; twin or triplet, 6.6%; ear infections requiring tympanostomy tubes, 2.6%; cephalohematoma, 1.0%; family history, 0.6%; seizures, 0.6%; and hydrocephalus, 0.5% (Table 2). Risk factors for DP have been reported to include assisted delivery, 3,8,10,12 plural births, 12 prolonged labor, 12 intrauterine constraint, 2 or unusual birth position.…”
Section: Discussionmentioning
confidence: 97%
“…They found similar results to our study in that the greatest number of patients were classified as type III (53%) followed by types IV, II, V, but they did not report type I in the study. 6 The mean age of referral and initial evaluation by a plastic surgeon was 5.9 months (median, 5.5, range, 0-78) with significant decrease in the mean age between the first 3 types. This is consistent with studies reporting the prevalence of DP peaks in the first 6 months of life.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a prospective study of 346 helmeted infants, Seruya et al [17] found a strong positive correlation between age at initiation and duration of helmet therapy. However, not all authors have observed a strict correlation [10,18,19] . As a result, it would appear that clinical decision-making regarding the start of helmet therapy in patients aged 4-8 months should be guided by the severity of the CVAI.…”
Section: Discussionmentioning
confidence: 99%
“…2 Since this campaign, the US rate of SIDS has decreased by 50% to 0.54 of 1000 live births. 3,4 However, this shift toward infant supine positioning has been thought to be associated with an increased incidence of deformational plagiocephaly (DP) seen in craniofacial centers throughout the United States. 2,[5][6][7] The prevalence of DP peaks in the first 6 months of life, involving up to 50% of infants.…”
mentioning
confidence: 99%